Formation of mesoporous silica nanoparticles with tunable pore structure as promising nanoreactor and drug delivery vehicle. Issue 16 (2nd February 2016) - Wu, Lu; Jiao, Zheng; Wu, Minghong; Song, Tingting; Zhang, Haijiao
Abstract : Mesoporous silica nanoparticles with tunable pore structures have been successfully fabricated by simply tuning the ethanol amounts in the precursor. Abstract : In this study, a series of mesoporous silica nanoparticles (MSNs) with well-defined morphologies and diverse pore structures have been successfully fabricated under alkaline conditions. In this case, cetyltrimethylammonium bromide (CTAB) was employed as the structure-directing agent, ethylacetate (EA) as the co-template, ethanol and water as co-solvents. By simply tuning the volume of ethanol in the reaction precursor, the trilobite-like nanoparticles, unique nanospheres with parallel and radical pores, and worm-like pore structure nanoparticles were obtained. The silica nanostructures were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), N2 adsorption–desorption measurement, etc. During the synthesis process, the lamellar micelles and microemulsion droplets formed in an oil–water (O/W) mixture played a key role for the formation of diverse MSNs. Additionally, the as-prepared MSNs showed good biocompatibility and high drug storage capability for ibuprofen (IBU) loading. More importantly, when used as a nanoreactor for constructing the novel functionalized Au@MSNs nanocomposites, they exhibited superior catalytic activities for the reduction of 4-nitrophenol (4-NP). The present findings could provide more possibilities for the controllable fabrication of silica nanomaterials and their potential applications.